2007
DOI: 10.3748/wjg.v13.i11.1701
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of main pancreatic duct dilation on computed tomography: Single and double duct dilation

Abstract: AIM:To study the patients with main pancreatic duct dilation on computed tomography (CT) and thereby to provide the predictive criteria to identify patients at high risk of significant diseases, such as pancreatic cancer, and to avoid unnecessary work up for patients at low risk of such diseases. METHODS:Patients with dilation of the main pancreatic duct on CT at Emory University Hospital in 2002 were identified by computer search. Clinical course and ultimate diagnosis were obtained in all the identified pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 13 publications
1
30
0
Order By: Relevance
“…21 We also acknowledge that although statistical significance was detected for the association of the PDG ratio and PC, the 95% CI for the PDG ratio was very wide due to small sample size of cancer cases (n = 34) which is the outcome of interest. On the basis of CT scan findings, it is very difficult to differentiate pancreatitis from PC based on the degree of pancreatic ductal dilation alone, although PD dilation could be slightly more prominent in patients with PC.…”
Section: Discussionmentioning
confidence: 92%
“…21 We also acknowledge that although statistical significance was detected for the association of the PDG ratio and PC, the 95% CI for the PDG ratio was very wide due to small sample size of cancer cases (n = 34) which is the outcome of interest. On the basis of CT scan findings, it is very difficult to differentiate pancreatitis from PC based on the degree of pancreatic ductal dilation alone, although PD dilation could be slightly more prominent in patients with PC.…”
Section: Discussionmentioning
confidence: 92%
“…One retrospective study showed that in 77 patients with ductal abnormalities on CT, 51 had isolated main pancreatic duct dilatation, of which 37 (73%) had chronic pancreatitis and two (4%) had pancreatic carcinoma. The 26 remaining patients had double duct dilatation, of which 15 (58%) had pancreatic carcinoma and three (12%) had chronic pancreatitis [8].…”
Section: Computed Tomographymentioning
confidence: 99%
“…[7] However, there are still many questions regarding the role of pancreatic cancer in dilation of the PD. In this study, we aimed to evaluate the significance of PD dilation on EUS, CT, or MRI in patients undergoing EUS for pancreatic indications.…”
Section: Introductionmentioning
confidence: 99%